FIRST REPORT OF SHEEP BOTFLY OESTRUS OVIS (LINNAEUS) (DIPTERA: OESTRIDAE) FROM THE NASAL SINUS OF SLAUGHTERED GOAT IN THE REPUBLIC OF YEMEN - Fahd Mohammed Abd Al Galil (Journal of Animal and Plant Sciences, 2023)
Many dipteran larvae are myiasis causing agents. These larvae can invade human and animal tissue. Nasal myiasis is caused by the larvae of Oestrus ovis (Diptera: Oestridae). Livestock raising is a tradition passed through generations and is practiced by the rural people in Yemen, especially in villages for economic earnings by selling them or slaughtering them as a source of meat. In a village Al-Khanf, Aridat Shari at Same'a District, Taiz Governorate, goats, sheep, and cows were sacrificed on Eid Al-Adha in 2021. About 50 larvae were recovered from the nasal canals of four sacrificed goats, 10 of which were placed in containers containing 50 ml of surgical alcohol 70% and brought to the laboratory. The larvae were dissected under a microscope. Following the identification keys, the posterior spiracles were mounted under the light microscope. The larvae were identified as sheep botfly O. ovis larvae. This is the first report of existence of O. ovis in Yemen, since no previously reported evidence of this fly in Yemen.
Keywords: Nasal myiasis; Oestrus ovis; Sheep Botfly; Oestridae; Taiz City; Yemen